Nuclear poly(A) binding protein 1 (PABPN1) and Matrin3 interact in muscle cells and regulate RNA processing. Issue 18 (7th September 2017) - Banerjee, Ayan; Vest, Katherine E.; Pavlath, Grace K.; Corbett, Anita H.
Abstract: The polyadenylate binding protein 1 (PABPN1) is a ubiquitously expressed RNA binding protein vital for multiple steps in RNA metabolism. Although PABPN1 plays a critical role in the regulation of RNA processing, mutation of the gene encoding this ubiquitously expressed RNA binding protein causes a specific form of muscular dystrophy termed oculopharyngeal muscular dystrophy (OPMD). Despite the tissue-specific pathology that occurs in this disease, only recently have studies of PABPN1 begun to explore the role of this protein in skeletal muscle. We have used co-immunoprecipitation and mass spectrometry to identify proteins that interact with PABPN1 in mouse skeletal muscles. Among the interacting proteins we identified Matrin 3 (MATR3) as a novel protein interactor of PABPN1. The MATR3 gene is mutated in a form of distal myopathy and amyotrophic lateral sclerosis (ALS). We demonstrate, that like PABPN1, MATR3 is critical for myogenesis. Furthermore, MATR3 controls critical aspects of RNA processing including alternative polyadenylation and intron retention. We provide evidence that MATR3 also binds and regulates the levels of long non-coding RNA (lncRNA) Neat1 and together with PABPN1 is required for normal paraspeckle function. We demonstrate that PABPN1 and MATR3 are required for paraspeckles, as well as for adenosine to inosine (A to I) RNA editing of Ctn RNA in muscle cells. We provide a functional link between PABPN1 and MATR3 through regulation of a common lncRNA target with downstream impact on paraspeckle morphology and function. We extend our analysis to a mouse model of OPMD and demonstrate altered paraspeckle morphology in the presence of endogenous levels of alanine-expanded PABPN1. In this study, we report protein-binding partners of PABPN1, which could provide insight into novel functions of PABPN1 in skeletal muscle and identify proteins that could be sequestered with alanine-expanded PABPN1 in the nuclear aggregates found in OPMD.